Therapeutic Vaccines in Non-Small Cell Lung Cancer: Immunologic Mechanisms, Therapeutic Platforms, and Barriers to Efficacy - Rumambi, Ekklesia Wulan Matilda; Tallei, Trina Ekawati; Turalaki, Grace Lendawati Amelia (Heca Sentra Analitika, 2026)
Therapeutic vaccines for non-small cell lung cancer (NSCLC) aim to improve treatment outcomes for a disease with high global incidence, mortality, and recurrence risk despite receiving standard multimodal therapy. This field focuses on the use of cancer antigens as vaccine targets in the context of immunology, influenced by immunovigilance, immunoreduction, and the tumor microenvironment, which suppresses the immune system. Mechanistic requirements for effective vaccination include selecting cancer antigens that are highly and homogeneously expressed, functionally linked to oncogenic pathways, and efficiently presented via MHC molecules to coordinate T cell responses. Peptide-based, dendritic cell-based, nucleic acid-based, and microbial vector-based vaccine platforms demonstrate safety and induction of antigen-specific cellular immunity responses. However, survival remains moderate and inconsistent, particularly in advanced-stage patients. Future progress will depend on rigorous, mechanism-based design that integrates data-driven antigen and epitope selection with tailored platform and route selection to shape the desired immune response, while also facilitating personalized and optimized vaccination strategies.